Respuestas

2013-07-31T02:13:42+02:00
Factor común (x-1)! + 2(x+1)x!       =  13
                     x(x-1)! - (x-1)!
(x-1)! + 2(x+1)(x)(x-1)!       =  13
      x(x-1)! - (x-1)!

(x-1)! [1+ 2(x+1)(x)]       =  13
      x(x-1)! - (x-1)!

Simplifico
 (x-1)!
 1+ 2(x^2+x)       =  13
      x-1
 2x^2+2x+1       =  13
      x-1
Tenemos ahora: 2x^2+2x+1    = 13(x-1)
                       2x^2+2x+1 = 13x -13
                       2x^2 - 11x+14 = 0
                        (2x - 7 )(2x - 4) 
                         -------------------- = 0
                                  2
(2x-7)(x-2)=0
x = 7/2  descartado porque factorial es para enteros positivos
x= 2